Meteorological patterns, technical validation, and chemical comparison of atmospheric dust depositions and bulk sand in the Arabian Gulf region. (15th January 2021) - Elsayed, Yehya; Kanan, Sofian; Farhat, Ahmad
Abstract: This study reports seasonal variations of meteorological parameters, atmospheric dust and dust-borne heavy metals concentrations measured, over a period of two years, next to two major airports (Dubai International Airport and Abu Dhabi International Airport) in the Gulf Cooperation Council (GCC) region. On-line monitoring stations were installed at each location next to dust samplers used to frequently collect PM2.5 and PM10 on Teflon filters for metal analysis. Clear seasonal variation in meteorological parameters were identified. The particulate matter concentrations depicted from the two locations were continuously monitored. The PM2.5 concentration ranged from 50 to 100 μg/m 3 on normal days but reached 350–400 μg/m 3 per day during mild storms. The PM10 levels ranged between 100 and 250 μg/m 3 during normal days and spiked to 750 μg/m 3 during mild storms. Energy Dispersive X-Ray Analysis (EDS) revealed the presence of significant amounts of alkali and alkaline earth metals, which pose potential harm to aircraft engines. ICP analysis showed the presence of heavy and toxic metals in concentrations that may pose harm to human health. Bulk sand samples from Abu Dhabi sites showed chemical similarities to the atmospheric dust samples. The concentrations of heavy metals, PM2.5, and PM10 are at levels that require further monitoring due to their impact on human health. The two years meteorological monitoring, with the seasonal variations, provided additional regional data in the Arabian Gulf. Furthermore, the study concluded that Sand and Dust storms (SDS) occur more frequently at the northern Arabian Gulf compared to its southern region. The chemical correlation between atmospheric dust and regional desert sand suggests the localized origin of the smaller dust particles that may form by breaking apart of the ground sand grains. As a result of the ongoing urbanization in the region, it is essential to collect additional data from various locations for a longer period of time. Graphical abstract: Image 1 Highlights: Seasonal variations in meteorological parameters and dust depositions were reported. PM measurements with optical monitoring and gravimetric methods showed similar trends. The measured atmospheric dust levels and their chemical composition were evaluated. Atmospheric dust depositions showed chemical similarity to regional bulk sand. Health risk associated with PM levels are moderate to high during sand storms.